Obesity After Kidney Transplantation—Results of a KTx360°Substudy - Nöhre, Mariel; Schieffer, Elisabeth; Hanke, Alexander; Pape, Lars; Schiffer, Lena; Schiffer, Mario; de Zwaan, Martina (Frontiers in Psychiatry, 2020)
Objective: There is solid evidence that kidney transplant (KTx) patients are susceptible to weight gain after transplantation. Post-transplantation obesity (BMI ≥ 30 kg/m2) seems to be associated with higher risks of hypertension, dyslipidemia, diabetes mellitus, and cardiovascular events, while there are contradicting findings regarding the association between obesity and mortality, graft failure after transplantation as well as other variables. We aimed to evaluate the course of weight after KTx and to assess the prevalence of post-transplant obesity in a large sample of German KTx patients. Further, we focused on potential associations between weight gain, obesity and BMI after transplantation with sociodemographic, medical, psychological (levels of anxiety and depression measured with the Hospital Anxiety and Depression Scale (HADS)), and donation-specific variables. Methods: In a structured post-transplant care program 433 KTx patients were evaluated at Hannover Medical School. Information on the pre-transplant body weight / dry weight of dialysis patients was taken from the electronic patient charts. At post-transplant assessment body weight was measured in the transplant center. For statistical analyses, descriptive statistics, analyses of variance, tests for correlations, and regression analyses were used. Results: Mean age was 51.3 years, 59% were male and 26.3% had ≥12 years of school attendance. Regarding somatic conditions 6.0% were suffering from type 2 diabetes mellitus, 6.9% were affected by NODAT and the mean estimated glomerular filtration rate (eGFR) was 47.7 ml/min/1.73m2. The prevalence rates of obesity before and after kidney transplantation were 14.8% and 19.9%, respectively. This represents an increase of 34%. Obesity after transplantation was associated with higher rates of type 2 diabetes mellitus and of new onset diabetes after transplantation (NODAT). Additionally, there was an association between increasing pre-transplant as well as post-transplant BMI and decreasing eGFR. Higher age and female sex were associated with higher rates of post-transplant obesity. Conclusions: Our results suggest that obesity represents a serious problem in KTx patients, especially regarding the association between increasing BMI and decreasing graft functioning (eGFR). However, this aspect is often overlooked and information on effective treatment options for these patients are scarce making further research on this topic necessary.